Study of the Rock Crack Propagation Induced by Blasting with a Decoupled Charge under High In Situ Stress - Xudong Li; Kewei Liu; Jiacai Yang (Advances in Civil Engineering)
The high in situ stress can significantly affect the blast-induced rock fragmentation and cause difficulties in deep mining and civil engineering where the drilling and blasting technique is applied. In this study, the rock crack propagation induced by blasting under in situ stress is first analyzed theoretically, and then a numerical model with a decoupled charge in LS-DYNA is developed to reveal how the initiation and propagation of rock cracks are under high in situ stress. Through simulation, the mechanisms of blast-induced crack evolution under various hydrostatic pressures and nonhydrostatic pressures are investigated, and the differences in crack evolution with specific decoupling coefficients are compared. According to the simulation, three damage zones, i.e., the crushed zone, the nonlinear fracture zone, and the radial crack propagation zone, are formed, and the radial crack evolution is greatly suppressed by the high in situ stress which has no much influence on the crack propagation in the crushed and the nonlinear fracture zones. The velocity of crack propagation is slightly reduced, and the process of crack propagation is stopped early when the rock is subjected to high in situ stress. Furthermore, the numerical analysis indicates that the crack grows preferentially in the direction of maximum principal stress, and the radial crack propagation is predominantly controlled by the preloaded pressure, which is vertical to the crack propagation direction. Based on the numerical results, it is suggested that the optimal decoupling coefficients for rock cracking are 2.65, 1.87, 1.37, and 1.22 for 0, 10, 20, and 30 MPa, respectively. This study provides not only an analysis of the rock crack evolution under high in situ stress but also a reference for resolving excavation difficulties in deep mining.